How Personality Can Improve APIP Supervisory’s Performance? Mediation Analysis Using Various Types of Competencies - Slamet Widodo; Wilysa Mardani; Gerry Suryosukmono; Lizar Alfansi; Fahrudin Js Pareke (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objectives: According to the holistic personality theory, the purpose of this study in general is to investigate the relationship between personality and competence in predicting the performance of the Regional Inspectorate Government Internal Supervisory Apparatus (APIP).Methodology: To investigate the relationship between variables, a survey of 180 respondents was conducted at 11 inspectorates in Bengkulu province. There were 123 auditors and 57 supervisors for local government administration among those who responded. Extroversion, neurotic, conscientiousness, openness, agreeableness, cognitive competence, emotional, social, generic, and supervisory performance are all investigated in this study. The structural equation model and the Sobel test were used to investigate the relationship between these variables. The model was created through an analysis of four new personality types, namely average, calm, selfish, and role models. This study discovered a link between personality and cognitive competence, cognitive competence and generic competence, and generic competence and supervisor performance.Finding: According to the findings, cognitive competence mediates the relationship between personality and generic competence, and generic competence mediates the relationship between cognitive competence and supervisor performance. Furthermore, it was discovered that the role model's personality has a positive effect on employees' cognitive competence.Conclusion: Inspectorate institution should improve its generic competence. The inspectorate must also engage in activities that promote cognitive competence, such as special training. The inspectorate must also plan training to improve employees' lack of personality.